Evaluation of Fecal Calprotectin, D-Lactic Acid and Bedside Gastrointestinal Ultrasound Image Data for the Prediction of Acute Gastrointestinal Injury in Sepsis Patients - Li, Junlu; Ren, Yanbo; Gao, Chang; Zhang, Kaili; Zheng, Fuwen; Kang, Jian (Frontiers in Medical Technology, 2021)
Objective: To investigate the early warning and prognostic evaluation of fecal calprotectin (FC), D-lactic acid, and bedside gastrointestinal ultrasound (B-GIUS) data for acute gastrointestinal injury (AGI) in sepsis patients. Main Method: Sepsis patients were grouped based on the presence or absence of AGI into AGI and non-AGI groups. Healthy volunteers of the same period were selected as the control group. FC, B-GIUS data, D-lactic acid, etc. were collected on the 1st, 3rd and 7th days of admission. Twenty-eight-day mortality was recorded. Main Results: FC, D-lactic acid levels, gastric antrum cross-sectional area, and small intestine wall thickness were significantly increased in group A and B (P < 0.05); furthermore, inner-to-outer diameter ratio and cross-sectional area of small intestine were lower than those in the control group (P < 0.05). FC, D-lactic acid, gastric antrum cross-sectional area and small intestine wall thickness in AGI group were higher than those in non-AGI group (P < 0.05). Inner-to-outer diameter ratio and cross-sectional area of small intestine in AGI group were smaller than those in non-AGI group (P < 0.05). There was no difference in the thickness, inner-to-outer diameter ratio nor the cross-sectional area ratio of colon between AGI and non-AGI groups (P > 0.05). AUC for D-lactic acid was 0.881, which was higher than FC's (0.74). When the D-lactic acid cutoff value was 22.16 μmol/L, the sensitivity was 77.9% and the specificity was 92% for the prediction of AGI in sepsis. AUC for the cross-sectional area of the gastrointestinal antrum was 0.657, which was higher than the small intestine thickness's (0.629). When the gastric antrum cross-sectional area was larger than 4.20 cm2, the sensitivity was 64% and the specificity was 65.3%. Conclusion: D-Lactic acid and FC were early diagnostic indicators for sepsis with AGI, and D-lactic acid was the superior indicator. The gastric antrum cross-sectional area and the small intestine wall thickness had an early warning effect, and the prediction of the gastric antrum cross-sectional area was superior to that of the latter. Because it is non-invasive and convenient, B-GIUS can help in the diagnosis of sepsis with AGI.